Bioequivalence Study of Phenyramidol Tablets - Olaganathan, Arjun Arumugam; Gunasekaran, Geetha Lakshmi; Thalapaneni, Nageswara Rao; Gopineedu, Srinivas; Yildirim, Ersin; Sari, Murat; Demir, Büşra (European Journal of Applied Sciences, 2026)
Phenyramidol is a benzyl alcohol derivative with central muscle relaxant and analgesic properties, used in the symptomatic treatment of acute painful muscle spasms associated with musculoskeletal conditions. This study aimed to evaluate the bioequivalence of a test formulation, Draxol® (Phenyramidol HCl 400 mg film-coated tablets, Santa Farma İlaç San. A.Ş., Turkey), against the reference product, Cabral® (Phenyramidol HCl 400 mg film-coated tablets, Recordati İlaç San.), under fed conditions. An open-label, randomized, two-treatment, three-sequence, three-period, single-dose, semi-replicate crossover design was employed in 42 healthy adult volunteers aged 20–45 years. A validated LC-MS/MS method was used to quantify plasma Phenyramidol concentrations across 21 sampling time points over 24 hours post-dose. Primary pharmacokinetic parameters — Cmax and AUC₀₋ₜ — were analyzed using Phoenix® WinNonlin v7.0, with statistical comparisons performed using SAS® v9.4. Of 42 enrolled subjects, 37 completed the study and 35 were included in the statistical analysis. The geometric mean Test/Reference ratios were 104.97% for Cmax and 100.12% for AUC₀₋ₜ, with 90% confidence intervals of 84.70–130.09% and 82.48–121.54%, respectively. No serious adverse events were reported, and both formulations were well tolerated. Bioequivalence was successfully demonstrated between the test and reference products, supporting the therapeutic interchangeability of Draxol® and Cabral® in clinical practice.